ТАРЖИМА ВА ТАРЖИМА МУАММОЛАРИ («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
Translation is the process of conveying the original information to the reader in an understandable way, the reader becomes the recipient of the information after reading the text, and a certain attitude is formed in relation to the information expressed in the text. This article discusses the problems of translation, translation studies and translation.
Keywords: translation, translation studies, pragmatic relations, translation problems, lexicography, linguistic analysis.